Efficacy of Supratarsal Injection of Triamcinolone Acetonide (Corticosteroid) for Treating Severe Vernal Keratoconjunctivitis (VKC) Refractory to All Conventional Therapy - Mirza Shafiq Ali Baig, Jameel A. Burney, Syed Shahab Ali (Pakistan Journal of Ophthalmology, 2010)
Purpose: To determine the efficacy of supratarsal injection of triamcinolone acetonide for treating severe Vernal keratoconjunctivitis (VKC) patients refractory to all conventional therapy. Material and Methods: The study was conducted at the Eye department of Sindh Government Qatar Hospital Orangi Town Karachi from January 2007 to April 2009. Eighteen patients of Vernal keratoconjunctivitis (VKC) resistant to all established therapy were included in the study. Patients presenting with signs and symptoms of the disease were clinically evaluated. They were given 0.5 ml (20 mg) of supratarsal injection of Triamcinolone acetonide. These cases were then evaluated and followed up for the relief of signs and symptoms of the disease and rise of intraocular pressure for a period of two years. Results: All patients experienced dramatic symptomatic relief from the disease. Reduction in cobblestone papillae by 50% was noted within three weeks after giving injection of corticosteroids in all patients. There was reduction in shield ulcer in 22% of patients and limbal involvement in 33% of patients in one to three weeks. No complications or side effects were observed. Conclusion: The dramatic clinical improvement, symptomatic relief from the disease and lack of increase in intraocular pressure suggest that supratarsal injection of corticosteroids may be a valuable therapeutic approach for the treatment of refractory VKC.